COMPANIES IN THE DATA WAREHOUSE IMPLEMENTATION - Marzuki Marzuki Marzuki (Majalah SIKOMTEK, 2004)
Data warehouse is a concept and a combination of technologies that facilitate theorganization to manage and maintain historical data obtained from the system or operationalapplications. Data warehouses collect historical data which can then be used as acomprehensive material for management to be able to take decisions, the analysis oforganizational needs, to forecasting organizations based on the data. Data warehouse allowsintegration of various types of data from a variety of applications or systems. This ensures theaccess mechanism 'one-stop shop' for management to obtain information and analyze it forthe decision organizational development. Within an organization, data warehouse can be usedas weapons in competing. This paper will discuss the implementation of data warehousewithin the company.